1989
DOI: 10.1159/000125241
|View full text |Cite
|
Sign up to set email alerts
|

Effect on Vasopressin Release of Microinjection of Angiotensin II into the Paraventricular Nucleus of Conscious Rats

Abstract: We have studied in conscious unrestrained rats the role of angiotensin II receptors in the paraventricular nucleus (PVN) in the control of vasopressin secretion under basal conditions and after 24 h of water deprivation. In euhydrated rats, the microinjection rostral to the PVN of 1 and 5 ng of angiotensin II produced a transient, dose-dependent increase in the plasma vasopressin concentration. There was also a transient, but not dose-dependent, rise in mean arterial blood pressure (MABP), without a change in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
11
0

Year Published

1990
1990
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(12 citation statements)
references
References 38 publications
1
11
0
Order By: Relevance
“…The slow response is consistent with electrophysiological studies showing that the reversal of ANG II-induced excitation of PVN sympathoexcitatory neurons following washout of the peptide requires several minutes (9,30). Alternatively, the slow time course could be explained by PVN AT1R blockade decreasing vasopressin secretion and its subsequent clearance from plasma, due to reversal of the known stimulatory effect of ANG II in PVN on vasopressin release (39,48). However, our finding that the greatest depressor responses to candesartan were observed in the more caudal regions of PVN, which house sympathoexcitatory neurons that project to the spinal cord and/or to RVLM, but contain few neurohypophysial magnocellular vasopressin neurons (20,35), argues against this possibility.…”
Section: Discussionsupporting
confidence: 82%
“…The slow response is consistent with electrophysiological studies showing that the reversal of ANG II-induced excitation of PVN sympathoexcitatory neurons following washout of the peptide requires several minutes (9,30). Alternatively, the slow time course could be explained by PVN AT1R blockade decreasing vasopressin secretion and its subsequent clearance from plasma, due to reversal of the known stimulatory effect of ANG II in PVN on vasopressin release (39,48). However, our finding that the greatest depressor responses to candesartan were observed in the more caudal regions of PVN, which house sympathoexcitatory neurons that project to the spinal cord and/or to RVLM, but contain few neurohypophysial magnocellular vasopressin neurons (20,35), argues against this possibility.…”
Section: Discussionsupporting
confidence: 82%
“…In addition, the excitation is abolished by the AT 1 antagonist losartan, demonstrating that ANG II's effects on this subset of PVN neurons are mediated by the AT 1 receptor. These observations are particularly intriguing given that the majority of studies thus far have concentrated on the actions of ANG II on magnocellular neurons (9,28,29,38). These reports have themselves garnered considerable debate with respect to AT 1 receptor localization with PVN.…”
Section: Discussionmentioning
confidence: 99%
“…Angiotensinergic fibers, cell bodies, and receptors have been reported in PVN (22,23,25,30,36,39), and ANG II has been shown to influence a variety of neuroendocrine and autonomic functions (7,11,12,23). Early reports have focused primarily on ANG II actions on magnocellular neurons (9,28,29,38). Interestingly, Lenkei et al (23)(24)(25) observed a high level of AT 1 receptor mRNA expression within the parvocellular areas of PVN and the surrounding periventricular area, but no expression in the magnocellular PVN.…”
mentioning
confidence: 99%
“…In rats, local administration of ANGII onto neurons of the PVN excites neurosecretory cells (Harding and Felix 1987) and increases plasma ADH level (Shoji et al 1989). Lesions of the PVN prevent the release of ADH in response to centrally applied ANGII (Iovino and Steardo 1985).…”
Section: Discussionmentioning
confidence: 99%